2020
DOI: 10.1002/ags3.12366
|View full text |Cite
|
Sign up to set email alerts
|

Current statement and safe implementation of minimally invasive surgery in the pancreas

Abstract: Minimally invasive pancreatic resection (MIPR) has become very popular even in pancreatic surgery. Laparoscopic pancreatoduodenectomy (LPD) and laparoscopic distal pancreatectomy (LDP) were introduced in 1994 and 1996, respectively. 1,2 Robotic surgical systems had also already been established 20 years ago, and the first case of robotic distal pancreatectomy (RDP) was reported in 2002. 3 Nowadays, laparoscopic and robotic approaches are becoming popular in MIPR, and the Miami international evidence-based guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 84 publications
(228 reference statements)
0
18
0
1
Order By: Relevance
“…In this study we investigated the real-world performance of laparoscopy in patients who underwent surgery for acute diffuse peritoni- Many studies, including ones that have used data from the NCD, have demonstrated the effectiveness of laparoscopy in the elective treatment of abdominal disease. [1][2][3] Laparoscopy is occasionally used for both diagnosis and treatment of abdominal disease in the emergency setting. 8,9,11 Diagnostic laparoscopy has been reported to be useful in the emergency setting because it can overcome the difficulty sometimes encountered in identification of the cause of acute abdomen by preoperative assessment using abdominal imaging methods such as ultrasound and computed tomography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we investigated the real-world performance of laparoscopy in patients who underwent surgery for acute diffuse peritoni- Many studies, including ones that have used data from the NCD, have demonstrated the effectiveness of laparoscopy in the elective treatment of abdominal disease. [1][2][3] Laparoscopy is occasionally used for both diagnosis and treatment of abdominal disease in the emergency setting. 8,9,11 Diagnostic laparoscopy has been reported to be useful in the emergency setting because it can overcome the difficulty sometimes encountered in identification of the cause of acute abdomen by preoperative assessment using abdominal imaging methods such as ultrasound and computed tomography.…”
Section: Discussionmentioning
confidence: 99%
“…Elective laparoscopic surgery is now widely performed for both benign and malignant disease because it is less invasive than open surgery and postoperative recovery is more rapid. 1 , 2 , 3 Laparoscopy has been reported to be useful in various surgical procedures, including gastrectomy and colectomy. 4 , 5 , 6 , 7 However, its usefulness in the emergency setting is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Analysen von High-Volume-Zentren legen sogar einen Vorteil der robotischen Technik in Bezug auf die postoperative Morbidität, sobald die Lernkurve, die sich auf bis zu 250 Fälle erstrecken kann, durchlaufen ist [15,16]. Etablierung der robotischen Pankreaschirurgie -Hürden und Fallstricke Die Etablierung der minimalinvasiven Pankreaschirurgie, robotisch oder laparoskopisch, erfordert zuallererst fundierte Expertise des Operateurs und des Zentrums in der offenen Pankreaschirurgie [17]. Wie bei allen komplexen viszeralchirurgischen Operationen wird eine Etablierung der robotischen Pankreaschirurgie durch begleitende Trainingsprogramme vereinfacht und beschleunigt [18,19].…”
Section: Hintergrundunclassified
“…Late diagnosis of PDAC can cause to lose the chance of surgical treatment and lead to a high mortality rate[ 78 ]. On the other hand, surgical treatments for PDAC can have a high morbidity and mortality rate.…”
Section: Ai In Survival Prediction and Response To Chemotherapymentioning
confidence: 99%